Factors Associated With the Occurrence and Evolution of Recent Small Subcortical Infarcts (RSSIs) in Different Locations - Hong, Hui; Zhang, Ruiting; Yu, Xinfeng; Jiaerken, Yeerfan; Wang, Shuyue; Luo, Xiao; Lou, Min; Huang, Peiyu; Zhang, Minming (Frontiers in Aging Neuroscience, 2020)
Recent small subcortical infarcts (RSSIs) can occur in different brain regions. Distinct etiologies might be involved for RSSIs in different locations and could further affect RSSI cavitation and functional outcomes. In this study, we aim to analyze the baseline clinical and imaging characteristics associated with the occurrence and cavitation of RSSIs in different locations. We retrospectively include patients who presented with RSSIs from a database for cerebral small vessel disease. Detailed information, including demographic, clinical, laboratory, and radiological data, were collected. We identify baseline RSSIs on diffusion-weighted images and divide them into brainstem, subcortical white matter, and basal ganglia region groups. Cavitation is evaluated on follow-up T2 fluid-attenuated inversion recovery (FLAIR) images. Statistical analysis is performed to determine factors associated with the occurrence and cavitation of RSSIs in different locations. We find that patients with brainstem RSSIs have a higher proportion of diabetes (64.1%) compared to patients with subcortical white matter (27.3%, P < 0.001) and basal ganglia region RSSIs (35.2%, P = 0.006) and have higher levels of HbA1c (7.20%) compared to patients with subcortical white matter (6.10%, P = 0.001) and basal ganglia region RSSIs (6.20%, P = 0.003). In addition, patients with brainstem RSSIs have higher NIHSS scores than patients with subcortical white matter RSSIs (2 vs 0, P = 0.001). Patients with subcortical white matter RSSIs have higher a white matter hyperintensity (WMH) burden compared to patients with basal ganglia region RSSIs (21.64 cm3 vs 11.10 cm3, P = 0.004). Follow-up analysis demonstrates that basal ganglia region RSSIs are less likely to cavitate than subcortical white matter RSSIs (61.4% vs 83.6%, P = 0.010), and contacting with WMH is associated with the cavitation of subcortical white matter RSSIs (OR: 101.760, P = 0.003). Our study demonstrates that RSSIs in different locations are associated with different clinical and imaging characteristics. Furthermore, cavitation of RSSIs might be affected by local lesion features and the surrounding environment rather than general demographic and clinical factors.